2014
DOI: 10.1007/s12471-014-0602-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device for end-stage heart failure: results of the first LVAD destination program in the Netherlands

Abstract: PurposeMechanical circulatory support with a continuous-flow left ventricular assist device (LVAD) may be a valuable treatment in end-stage heart failure patients for an extended period of time. The purpose of this study was to evaluate the safety and efficacy of implantation of a continuous-flow LVAD in end-stage heart failure patients within the first destination program in the Netherlands.MethodsA third-generation LVAD was implanted in 16 heart failure patients (age 61 ± 8; 81 % male; left ventricular eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…By depicting the set-up of our program, we sought to provide practical elements for similar-sized centers wishing to implement a mechanical-circulatory-support program for DT. To our knowledge, only a few center’s experience of establishing an LVAD-program are available with long-term results in the literature, and none specifically for DT [ 16 21 ]. Those available with long-term results usually concerned older-generation devices with different implantation strategies from those in our study (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…By depicting the set-up of our program, we sought to provide practical elements for similar-sized centers wishing to implement a mechanical-circulatory-support program for DT. To our knowledge, only a few center’s experience of establishing an LVAD-program are available with long-term results in the literature, and none specifically for DT [ 16 21 ]. Those available with long-term results usually concerned older-generation devices with different implantation strategies from those in our study (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular assist devices (LVADs) have increasingly become part of the arsenal in the treatment of end-stage heart failure [ 1 3 ]. Despite advances in pump technology, thromboembolic events and acute pump thrombosis remain potentially life-threatening complications [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study (Haeck et al, 2015) reported a survival rate of 75% at 6 months, and the eighth INTERMACS report (all indications, n=15,000) showed that actuarial 1-year survival for continuous-flow LVADs was 80% (Kirklin et al, 2017). The survival rate in the present study was slightly higher than in a previous study (Haeck et al, 2015; Nakatani et al, 2017) and the INTERMACS report (Kirklin et al, 2017), but the small sample size should be considered in comparing survival rates. The most common cause of death was a neurological disorder, followed by multiple system organ failure, infection, device malfunction, and right heart failure (Kirklin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life has become an important parameter in evaluating clinical outcomes in LVAD recipients. Several studies (Haeck et al, 2015; Kato et al, 2015; Kirklin et al, 2017; Mahfood Haddad et al, 2017) demonstrated that quality of life after implantation was significantly improved in the physical and mental components. In our study, the quality of life measured at 12 months using the Minnesota Living with Heart Failure Questionnaire after implantation also showed improvement in both physical and mental components.…”
Section: Discussionmentioning
confidence: 99%